Some Mineralogical Characteristics of the Egyptian Black Sand Beach Ilmenite Part I: Homogeneous Ilmenite and Titanhematite-Ferriilmenite Grains - Moustafa, M. I. (Engineering, Technology & Applied Science Research, 2022)
The high-grade Egyptian beach ilmenite concentrate contains various mineral textures in addition to the main homogeneous ilmenite grains (63%), which may contain solid solutions of geikielite (MgTiO3) and pyrophanite (MnTiO3) mineral components. Few homogeneous ferrilmenite grains (2%) associated with the concentrated ilmenite grains are detected. The contents of Fe2O3, MgO, Al2O3, and Cr2O3 in the ferrilmenite grains range between 7.3% and 22.8%, 3.4% and 6.6%, 0.2% and 0.7%, and 0% and 1.2% respectively. The detected hematite-ilmenite exsolved intergrowths (21.4%) have titanhematite exsolutions of different shapes, sizes, and orientations. They occupy 5%-40% of the whole intergrowth and may show one or two distinct generations. In some ferrilmenite components, MnO ranges between 1.5% and 8.6%. The Cr2O3 and Al2O3 contents range between 0% and 1.2% and 0% and 3.2% respectively. They are mostly between 0% and 0.1% for either of the ferrilmenite components, while relatively greater content is present in the titanhematite components. In some grains, the titanhematite exsolution bodies are replaced by goethite or hydrated iron oxides. In others, the ferrilmenite intergrowth may be partially or completely altered into leucoxene. Some minor composite grains are detected in the concentrate, where each grain consists of two parts, one part is titanhematite-ferrimenite and the other is ferrilmenite-titanhematite. The titanhematite exsolved components have relatively lower TiO2 content (5.8%-23.8%). Both MgO and MnO are positively correlated with FeO rather than Fe2O3. The presence of sphenes in the obtained ilmenite concentrate may be responsible for the recorded amounts of SiO2 (30.1%-30.8%) and CaO (28.1% and 28.8%). The Cr2O3 content is relatively much higher in sphene spots than in ilmenite spots, ensuring that Cr2O3 neither follows TiO2 nor FeO. The nature of the problem of the relatively lower Ti content and the relatively higher Fe and Cr contents of the obtained ilmenite concentrates is the target of the article. The problem is related to the mineralogy of ilmenite or to the used physical concentration flowsheet of the separated concentrate and the ability to improve the ilmenite concentrate’s specifications. It is concluded that although the homogeneous ilmenite is characterized by low Cr2O3 content, some of the other exsolved texture components, e.g. titanhematite and sphenes, have relatively higher Cr2O3, in addition to Fe2O3, SiO2, or CaO. They can negatively affect the marketable specifications of the separated Egyptian black sand ilmenite concentrate.